Schistosomiasis Causes Remodeling of Pulmonary Vessels in the Lung in a Heterogeneous Localized Manner: Detailed Study. (1st April 2013) - Kolosionek, Ewa; King, Jayne; Rollinson, David; Schermuly, Ralph Theo; Grimminger, Friedrich; Graham, Brian B.; Morrell, Nicholas; Butrous, Ghazwan
Abstract : Schistosomiasis is a global parasitic disease with high impact on public health in tropical areas. Schistosomiasis is a well‐described cause of pulmonary arterial hypertension (PAH). The exact pathogenesis is still unclear, though inflammatory mechanisms are suspected. Another unknown is whether the changes in the pulmonary vasculature are generalized or localized. We studied 13 mice infected with cercariae for 12 weeks compared with 10 control mice. In our model, we observed that the liver was a target during infection and was enlarged more than two‐fold after infection. However, right heart hypertrophy as measured by RV/(LV + S) ratio was not observed at this time point. Moreover, we noticed that 72% of the sampled lobes (92% of the lungs) harvested from these animals costained evidence of granulomatous changes, secondary to egg deposition. We systemically mapped the distribution of granulomatous lesions in right lung lobes ( n = 43) of infected mice. We observed that the distribution of the granulomatous lesions was heterogeneous. Remodeled pulmonary vessels were seen in 26% of the lobes (46% of the lungs) and were observed only in close proximity to the granuloma. No remodeling was observed in the absence of granulomas. These findings support the view that pulmonary vascular remodeling is caused by the local presence of granulomas in PAH associated with schistosomiasis. The heterogeneous nature of the remodeling partly explains why many patients with schistosomiasis do not develop pulmonary hypertension.